Phenotypic characteristics of the mycelium of Pleurotus geesteranus using image recognition technology - Wang, Xingyi; Xu, Ya; Wei, Xuan (Frontiers in Bioengineering and Biotechnology, 2024)
Phenotypic analysis has significant potential for aiding breeding efforts. However, there is a notable lack of studies utilizing phenotypic analysis in the field of edible fungi. Pleurotus geesteranus, as a lucrative edible fungus with significant market demand and substantial industrial output, early-stage phenotypic analysis is imperative during its breeding process. This study utilizes image recognition technology to investigate the phenotypic features on mycelium of Pleurotus geesteranus. We aim at establishing the relations between these phenotypic characteristics and mycelial quality. Four groups of mycelium, including the non-degraded and degraded mycelium, the 5th and 14th subcultures are used as image sources. Two categories of phenotypic metrics, outline and texture, are quantitatively calculated and analyzed. In the outline features of the mycelium, five indices such as the mycelial perimeter, radius, area, growth rate and change speed, are proposed to show the mycelial growth. In the texture features of the mycelium, five indices such as mycelial coverage, roundness, groove depth, density and density change are raised to analyze the phenotypic characteristics of the mycelium. Moreover, we also compared the cellulase and Laccase activities of the mycelium, and found that the cellulase was consistent with the phenotypic indices of the mycelium, which further verified the accuracy of digital image processing technology in analyzing the phenotypic characteristics of mycelium. The results indicate that there are significant differences in these ten phenotypic characteristic indices (P<0.001), elucidating a close relationship between the phenotypic characteristics and the mycelial quality. This conclusion facilitates the rapid and accurate strain selection in the early breeding stage of Pleurotus geesteranus.